(untitled) (Experimental biology, 2024)
The present study provides a comprehensive account of the advancement and utilization of guide RNAs (gRNAs) through the utilization of CRISPR/Cas systems in the identification of two prominent apple viruses, namely Apple Chlorotic Leaf Spot Virus (ACLSV) and Apple Stem Pitting Virus (ASPV). The presence of these viruses presents significant risks to the worldwide apple production industry, due to their adverse effects on fruit quality and yield. The primary objective of this study is to investigate the utilization of CRISPR technology, namely the CRISPR/Cas12a and Cas13a systems, when employed for accurate and highly sensitive diagnostic applications. The present methodology focuses on exploiting conserved areas within the viral genome to improve the efficacy of detection. The methodology involves the development of guide RNAs (gRNAs) that selectively bind to conserved areas within the viral genomes of ACLSV and ASPV. This is achieved by the application of bioinformatics techniques, which aim to reduce unintended effects and enhance the specificity of the targeting. The first stage of in vitro testing entails the production of synthetic viral RNA, followed by live plant testing to verify the efficacy of the gRNAs in real-world settings. Furthermore, the research project includes the generation of complete cDNA clones of the viruses in order to enhance comprehension of their genomic architectures, a critical aspect in the improvement of gRNA designs. This study highlights the incorporation of sophisticated genomic methodologies alongside conventional virology approaches in order to enhance the identification and control of plant viral illnesses. The objective is to enhance agricultural well-being and productivity by develop novel diagnostic strategies.